03 Opioid overdose death in wales from 2012 to 2015: a linked data autopsy study. Issue 10 (24th September 2019) - Jones, Matthew; Watkins, Alan; Bulger, Jenna; John, Ann; Snooks, Helen; Bradshaw, Ceri; Fuller, Gordon
Abstract : Background: Opioids account for more fatalities by overdose than any other drug. Fatal opioid overdose is a growing public health problem, with incidence rising in western countries especially. We sought to describe the deaths, sociodemographic characteristics, and service usage patterns of decedents of opioid overdose in Wales. Methods: We carried out a retrospective cross-sectional analysis of opioid related deaths in Wales identified from Office for National Statistics data between 01/01/2012 and 31/12/2015, in Wales, UK. Routine data were captured from Office of National Statistics (ONS), the Welsh Demographic Service and National Health Service datasets for the preceding three years and linked using a deterministic algorithm. Demographic, socioeconomic, clinical and service use characteristics were detailed using descriptive statistics. Results: The majority of opioid overdose deaths (n=312) occurred at home (n=253, 81.09%) and were accidental (n=262, 83.97%). A third (31.09%) involved heroin as the main object of injury (n=97). Decedents were mostly male (n=228, 73.1%) and lived in socioeconomically deprived (lacking in material and social opportunities and/or resources) areas at the time of their death (n=199, 63.75%). The majority of decedents changed address at least once during the 36 month observation period prior to death (n=169, 53.85%), but rarely moved far geographically (e.g. were resident in more than two postcode areas). The majority of decedents visited the emergency department (n=227, 72.76%), were admitted to hospital (n=199, 63.78%) – usually for mental health problems – and were recorded at least one General Practitioner episode (n=258, 82.69%) during the observation period. A minority of decedents used drug treatment services (n=72, 23.08%). Conclusions: Opioid overdose deaths occur most commonly secondary to heroin use. Decedents demonstrate a peripatetic lifestyle and are rarely engaged with drug treatment services. Frequent contact with unscheduled care providers might present a target for preventative interventions.